Vitamin D3 Supplementation Increases Fibroblast Growth Factor-23 in HIV-Infected Youths Treated with Tenofovir Disoproxil Fumarate. Issue 6 (August 2014) - Havens, Peter L; Hazra, Rohan; Stephensen, Charles B; Kiser, Jennifer J; Flynn, Patricia M; Wilson, Craig M; Rutledge, Brandy; Bethel, James; Pan, Cynthia G; Woodhouse, Leslie R; Van Loan, Marta D; Liu, Nancy; et al.
Background: Tenofovir (TDF) is associated with phosphaturia and elevated 1, 25 dihydroxy vitamin D (1, 25-OH(2)D). Fibroblast growth factor 23 (FGF23) causes phosphaturia and increases in response to elevated 1, 25-OH(2)D. Vitamin D-binding protein (VDBP) binds to 1, 25-OH(2)D, decreasing its biological activity, and is elevated in individuals with higher plasma tenofovir concentrations. We compared FGF23 and VDBP before and after vitamin D3 (VITD) supplementation in youths treated with combination antiretroviral therapy (cART) containing or not containing TDF. Methods: A randomized controlled trial in HIV-positive youths aged 18–25 years enrolled participants based on cART treatment with TDF (TDF; n =118) or without TDF (no-TDF; n =85), and randomized within those groups to VITD (50, 000 IU every 4 weeks) or placebo (PL). We measured FGF23 and VDBP and calculated free 1, 25-OH(2)D at baseline and week 12, and compared changes by TDF treatment and VITD randomized group. Results: At baseline, serum FGF23 concentration showed a quadratic relationship with 1, 25-OH(2)D most pronounced in the TDF group. At week 12, total and free 1, 25-OH(2)D increased in the VITD but not PL groups, independent of TDF use. FGF23 increased in the TDF group receiving VITD, but there was no FGF23 change in the no-TDF group receiving VITD or the PL groups. The adjusted mean change in FGF23 from baseline to week 12 was 7.7 pg/ml in the TDF/VITD group, compared with -1.7 (no-TDF/VITD, P =0.010), -1.3 (TDF/PL, P =0.006) and 1.1 (no-TDF/PL, P =0.035). Conclusions: These results suggest that TDF-containing cART may alter the FGF23 response to vitamin D supplementation in HIV-infected youths. Clinical trials number: NCT00490412.